Optimalisasi Aktivitas dan Hasil Belajar Peserta Didik pada Mata Pelajaran Biologi KD. 3.9/4.9 Evolusi Melalui Model Project Based Learning Metode Focus Group Discussion pada Kelas XII.MIA.1 MAN 2 Kota Payakumbuh Semester Genap Tahun Pelajaran 2021/2022 - Novia Erlinda (Departement of Mathematics Education, 2022)
The aim of study this classroom action research is to find out whether the Project Based Learning Model Focus Group Discussion method can improve the activities and learning outcomes of students class XII .MIA.1 MAN 2 Payakumbuh even semester 2021/2022 academic year. This research with two cycles. The results of observing student activities showed a significant increase, from 44.31% in the first cycle to 79.36% in the second cycle. The results of learning knowledge show that in the first cycle the average learning outcomes of students' knowledge is 84.67. Up by 8.55% from pre-cycle. Completeness from pre-cycle to cycle I increased from 19 students in pre-cycle to 28 students with a percentage increase of 17.39%. Furthermore, in the second cycle the average learning outcomes rose to 92.33 from the first cycle with a percentage increase of 9.05% with an increase in completeness from 28 people to 100% complete from 30 students. The percentage increase in completeness is 7.15%. For skills learning outcomes, the average skills learning outcomes are also almost the same as knowledge learning outcomes. The data showed that in the first cycle the average student learning outcomes were 84.67, an increase of 11.10% from the pre-cycle. Completeness from pre-cycle to cycle I also increased from 23 students in the pre-cycle to 27 students with a percentage increase of 17.42%. In the second cycle, the average learning outcomes rose to 96.37 (very good category) from the first cycle with a percentage increase of 9.80% with an increase in completeness from 27 people to complete 100% with the same number of students. The percentage increase in completeness is 11.11%. The conclusion obtained from this research is that the learning model of the Project Based Learning Model Focus Group Discussion method can increase the activities and learning outcomes of students.